Overcoming fear of speaking in english through meaningful activities: a study with teenagers (2008)
This article reports on a study implemented in a public school to explore some learning strategies to overcome speaking fears and anxiety. After a preliminary inquiry to find out the possible causes of the problem, we proposed an artistic and academic space called Cultural Moment, adapted from the Spanish class. It is a task-based cooperative learning environment. The students have the possibility to try their aesthetic abilities and interact in English within an unstressful and enjoyable atmosphere. To gather information we used interviews, field notes, and audio and video recordings. This study suggests some possible strategies to reduce language anxiety and promote oral interaction in the classroom. Keywords: Learning strategies, cultural activities, overcoming fears, cooperative learning, oral interaction Este artículo da cuenta de un estudio que se realizó en un colegio oficial para explorar algunas estrategias de aprendizaje con el propósito de superar el miedo y la angustia al hablar. A partir de una indagación respecto a las posibles causas del problema se abre un espacio artístico y académico denominado Momento Cultural, inspirado en la clase de español. Las actividades de clase se desarrollan en un ambiente de aprendizaje cooperativo basado en tareas. Los estudiantes tienen la posibilidad de mostrar sus habilidades estéticas e interactuar en inglés en una atmósfera de confianza y alegría. La recolección de información se hizo a través de entrevistas, grabaciones de video y audio y notas de campo. El estudio sugiere algunas posibles estrategias para reducir la ansiedad y promover la interacción oral. Palabras clave: Estrategias de aprendizaje, actividades culturales, interacción oral, superación de miedos, aprendizaje cooperativo